State administration and the founding fathers during the critical period - Beach, John C. (1997)
Some scholars stress the absence of discussion in the U.S. Constitution of public administrative institutions, concluding that bureaucracy's role in American government is thereby legally and historically suspect. An important insight on this point can be gained by examining public administration activities in the 13 original states during the "Critical Period" between the Declaration of Independence and the Constitutional Convention. Administrative arrangements were surprisingly elaborate during this period, although not necessarily housed under an executive branch. Moreover, state governments already were performing - by means of these arrangements - almost all of the powers explicitly enumerated in the new federal government. The Founding Fathers, far from being ignorant of prevailing state administrative institutions or their activities in these areas, were immersed in them. Hence they must have clearly understood what would be required administratively of the new federal government. - Reproduced
Keywords: Public administration - United States; Public administration